Слово и немота в русской (пост)культуре. Кысь Татьяны Толстой - Filimonova, Alexandra; Mazhitaeva, Shara (Przegląd Wschodnioeuropejski, 2023)
This article analyzes the use of intertextuality as one of the ways to explicate the concept of a “book” in the novel The Slynx by Tatyana Tolstaya. Introducing the texts of the previous culture is considered a genre characteristic of the dystopian discourse. Using the example of Pushkin’s text presented in the novel in various forms, some techniques and functions of contextual transformation of the “book word” are analyzed. Modal and semantic reaccentuation of important elements of the language reality, on the one hand, destroys the logocentric paradigm of Russian culture and reveals the consequences of the cultural rupture and further obliteration. On the other hand, it provides the unity of a national linguistic and cultural universe. Searching to discover the constants of the national mentality, the novel shows the indissoluble connection between spiritual search and violence. The usurpation of the words of the past culture turns into cultural and spiritual dumbness.